Can tax agents support tax compliance in low‐incomecountries? Evidence from Uganda - Giovanni Occhiali; Fredrick Kalyango (Wiley, 2023)
Tax agents' role in ensuring or deterring compliance with tax obligations has received relatively little attention in the literature. Some evidence has emerged indicating when agents improve (or decrease) compliance, and why taxpayers employ their services. However, most existing studies have focused on high‐ or upper‐middle‐income countries. As the tax systems of low‐income countries present a unique set of compliance issues, a closer look at the role that tax agents play in these contexts is warranted. In this paper, we present evidence from two surveys on their use in Uganda. Our results show that tax agents contribute to an increased quality of filed returns thereby leading to lower audit adjustments The type of services more frequently requested by taxpayers seem to match those in high‐ income countries, as do their reasons for engaging tax agents in the first place.
Keywords: low‐income countries; tax agents; tax compliance; Uganda